Mater ialism and Happiness: Vedic vs. Contemporary Perspective - Agrawal, Shuchi; Garg , Devika (Gyan Management Journal, 2010)
Material acquisitiveness has become the primary goal in modern society. Striving for money has increased greed and competition among people. It has even affected the corporate world. People and organizations have started equating money with achievement and happiness. Is it really a coincidence that there have been so many international corporate scandals in the past years? Are people really happy? This paper tries to explore the culture of increasing greed for money and material goods amongst people and its effect on happiness from Vedic as well as contemporary perspective. It further tries to consider the best approach in such a situation.